2022
DOI: 10.1038/s41467-022-32321-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immunogenicity and reactogenicity of heterologous ChAdOx1-nCoV-19-priming and BNT162b2 or mRNA-1273-boosting with homologous COVID-19 vaccine regimens

Abstract: Comparative analyses of the immunogenicity and reactogenicity of homologous and heterologous SARS-CoV-2 vaccine-regimens will inform optimized vaccine strategies. Here we analyze the humoral and cellular immune response following heterologous and homologous vaccination strategies in a convenience cohort of 331 healthy individuals. All regimens induce immunity to the vaccine antigen. Immunity after vaccination with ChAdOx1-nCoV-19 followed by either BNT162b2 (n = 66) or mRNA-1273 (n = 101) is equivalent to or m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 37 publications
5
45
0
Order By: Relevance
“…This observational study included 22 healthy immunocompetent individuals, who received the NVX-CoV2373-vaccine as a standard two-dose regimen as per German recommendations [2]. Individuals after dual vaccination with BNT162b2 (n=22) and mRNA-1273 (n=22) matched for age and gender served as controls and were derived in part from convenience cohorts as described before [8, 9] (table 1). All individuals had no known history of SARS-CoV-2 infection and were negative for nucleocapsid-specific IgG.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This observational study included 22 healthy immunocompetent individuals, who received the NVX-CoV2373-vaccine as a standard two-dose regimen as per German recommendations [2]. Individuals after dual vaccination with BNT162b2 (n=22) and mRNA-1273 (n=22) matched for age and gender served as controls and were derived in part from convenience cohorts as described before [8, 9] (table 1). All individuals had no known history of SARS-CoV-2 infection and were negative for nucleocapsid-specific IgG.…”
Section: Resultsmentioning
confidence: 99%
“…Lower CD4 T-cell levels were associated with a significantly lower expression of CTLA-4 and a lower percentage of multifunctional cells. We have previously shown that the phenotypical and functional profile of antigen-specific T cells correlated with antigen-load during active infections [15, 16] or vaccination [8, 9, 17] to counteract excessive T-cell proliferation or immunopathology. Therefore, the phenotypical and functional differences may indicate a lower extent of antigen encounter during the induction phase in NVX-CoV2373-vaccinated individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations